PERSEPSI MAHASISWA AKUNTANSI MENGENAI FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK, AKUNTAN PENDIDIK, AKUNTAN PERUSAHAAN DAN AKUNTAN PEMERINTAH - Hutadjulu, Linda Yuliana (Fakultas Ekonomi, Universitas Cenderawasih, 2018)
This research was conducted to determine the Perception of Accounting students at FEB UNCEN. Data in this study were obtained from questionnaires with accounting student respondents who were in the sixth semester (6). Respondents numbered 91 people who were sampled in this study. The results of this study indicate there are no differences in views between students who choose careers as public accountants, educating accountants, corporate accountants and government accountants, regarding the factors of Financial Awards, Work Environment, Labor Market Considerations andPersonality. As for the factors of Professional Training, Professional Recognition, and Social Values, there are different views.